2013
DOI: 10.1016/j.jtcvs.2012.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Control of ventricular unloading using an electrocardiogram-synchronized Thoratec paracorporeal ventricular assist device

Abstract: The timing of pump ejection in synchronized mode yields control over left ventricular energetics and can be a method to achieve gradual reloading of a recoverable left ventricle. The traditionally suggested counterpulsation is not optimal in ventriculo-aortic cannulation when maximum unloading is desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
2
21
3
1
Order By: Relevance
“…The effect of the timing of the ejection phase of such a pulsatile volume-displacement VAD on the stroke work and the aortic valve flow was demonstrated earlier in vivo [43]. Similarly to the results in the current paper, that analysis shows that a change in phase shift is required when the maximization of the aortic valve flow was assigned preference over the minimization of the left ventricular stroke work.…”
Section: Constant Speed Solutionsupporting
confidence: 81%
“…The effect of the timing of the ejection phase of such a pulsatile volume-displacement VAD on the stroke work and the aortic valve flow was demonstrated earlier in vivo [43]. Similarly to the results in the current paper, that analysis shows that a change in phase shift is required when the maximization of the aortic valve flow was assigned preference over the minimization of the left ventricular stroke work.…”
Section: Constant Speed Solutionsupporting
confidence: 81%
“…Previous studies have investigated synchronization ratios (1:2 and 1:4) lower than the HR under one given phase-shift setting [24] with the intention of establishing a weaning protocol. The importance of considering the pump timing and systolic fraction as an integral part of the investigation has been shown in vivo by [2] for pVADs and by [1,3,4,26,33,34] both in silico and in vivo for tVADs.…”
Section: Discussionmentioning
confidence: 99%
“…They found the best ventricular unloading in terms of hydraulic stroke work (SW) during asynchronous operation with the stroke frequency in the same range as the patient's HR. This investigation was further assessed by Heredero et al [14] and Amacher et al [2], who found that under synchronous operation the timing between ventricle and pump systole has a remarkable impact on the unloading of the left ventricle in terms of hydraulic SW. This influence was not investigated in [24].…”
Section: Introductionmentioning
confidence: 97%
“…52/09). Eight adult, female, mixed breed sheep (59 -83 kg) were implanted with a Thoratec PVAD (Thoratec, Pleasanton, CA) via left thoracotomy as described in detail previously (3). A custom-made cannula was inserted in the LV apex of the beating heart, and an outflow graft was anastomosed end-to-side on the aorta.…”
Section: Animals This Study Was Approved By the Commission Of Animalmentioning
confidence: 99%
“…In addition to being used as a bridge-to-transplantation, the use of VADs as a bridge-to-recovery and as an alternative to heart transplantation is becoming increasingly important (14). The impact of VADs on the hemodynamics and on the mechanical unloading of the heart has been analyzed previously (3,7,12,16,26). In cases where the duration of VAD support is in the order of years, its impact on the peripheral circulation and potentially induced structural changes (8,11,22) needs more research.…”
mentioning
confidence: 99%